Pengaruh Transformational Leadership terhadap Job Performance dengan Work Engagement sebagai Variabel Mediasi - Insyra, Tasya Rania (Jurnal Ilmu Manajemen, 2022)
This study aims to determine and analyze the relationship between transformational leadership and job performance and whether work engagement mediates the relationship between transformational leadership and job performance. The number of samples in this study was 55 employees. Statistical analysis used Partial Least Square (PLS) with SmartPLS 3.0. The measurement scale uses a Likert Scale. The survey results show that transformational leadership has no significant effect on job performance. Transformational leadership has a considerable effect on work engagement. Work engagement has a significant impact on job performance. Work engagement as a mediator variable significantly affects the relationship between transformational leadership and job performance. Transformational leadership is not directly related to job performance but is mediated by work engagement. The research implication that can be applied is that companies need to provide regular training programs, provide rewards and tiered career development, and create a comfortable work environment to improve employee job performance and engagement.